Strategi Peningkatan Sumber Daya Manusia Melalui Pendidikan Studi Kasus Kampus Cabang Universitas Darwan Ali Di Kabupaten Katingan - Abdul Azis (Politeknik Sampit, 2022)
Indonesia is one of the countries that is committed to achieving Education for All Higher Education Collaboration with Regional Governments, because the enactment of the Regional Autonomy Law provides wider opportunities for local governments to manage all resources in the regions. This condition provides opportunities for local governments to take advantage of tertiary institutions as strategic partners. Cooperation is built between local governments and universities in various forms and interests. Such as the distance to the provincial capital which is too far, as felt by the community in Central Kalimantan, especially those in the area,) through the implementation of research and community service to carry out the Tri Dharma of Higher Education. The collaboration is realized by opening a branch campus in the Katingan district. The good news is that even though you study at a branch campus, the degree you get is still accredited by the main campus, if you want to get a degree from Darwan Ali University, you don't need to study far away, just study at the Darwan Ali University branch campus. This research was conducted using qualitative research methods. The research method used to examine the condition of natural objects where the researcher is the key instrument. Meanwhile, for data techniques using observation techniques, documentation, and in-depth interviews. Darwan Ali University plays an important role in it, realizes expectations, has integratedness in the development of the vision and mission of education to develop human resources in Katingan Regency, according to the Rector of the University of Darwan Ali, Dr. Ali Kusuma, if since the establishment of the university, his party has committed to prioritizing students who graduate with quality and competitiveness. During the rectification process for Civil Servants (PNS) in various regions several years ago, he said that it was not uncommon for students to be accepted by Darwan Ali University alumni. The latest data shows that the Katingan branch of Darwan Ali University has 200 new students, and 80 people are village officials throughout the Katingan Regency.